2010
DOI: 10.1097/brs.0b013e3181cbcc10
|View full text |Cite
|
Sign up to set email alerts
|

Costs of School Scoliosis Screening

Abstract: This was the largest study that has evaluated school scoliosis screening on students who were followed during their adolescence and accounted for all relevant costs. The cost per student screened in the scoliosis screening program in Hong Kong was comparable to that in Rochester, which had a similar protocol and was evaluated in a similar manner. The estimated costs can help the policy makers when they allocate healthcare resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
0
26
0
3
Order By: Relevance
“…The cost of a scoliosis screening program for 1473697 adolescents in Minnesota in 1982 was low, averaging 6.6 cents per student screened 6. Among 115190 adolescents in Hong Kong in 2010, the costs of screening and diagnosing a child with a scoliosis were $17.94 and $2.08, respectively 28. Both studies concluded that their scoliosis screening program was cost effective 6,28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of a scoliosis screening program for 1473697 adolescents in Minnesota in 1982 was low, averaging 6.6 cents per student screened 6. Among 115190 adolescents in Hong Kong in 2010, the costs of screening and diagnosing a child with a scoliosis were $17.94 and $2.08, respectively 28. Both studies concluded that their scoliosis screening program was cost effective 6,28.…”
Section: Discussionmentioning
confidence: 99%
“…Among 115190 adolescents in Hong Kong in 2010, the costs of screening and diagnosing a child with a scoliosis were $17.94 and $2.08, respectively 28. Both studies concluded that their scoliosis screening program was cost effective 6,28. However, the average cost of finding one child with a scoliosis of 5 degrees or more was $194 in the scoliosis screening program of 29195 adolescents in Quebec, Canada in 1985 18.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the available data [8-10,12,16,17], the estimated cost of school screening for scoliosis ranges from less than USD 1.00 to more than USD 30.00 per child screened. The lower estimates considered calculations for conducting screening program per se , borne by the screening centers or schools.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, observation and care are greatly important to prevent deformities from developing in the acceleration phase. Therefore, school screening for scoliosis is suggested in the growth period, especially during the age of bone development, which is 11 years for girls and 13 years for boys, to minimize economy loss13, 15 ) . The purpose of this research was to assess the actual conditions of the diagnosis and treatment of scoliosis by focusing on middle-school students in order to provide a basis for active education and treatment of scoliosis through school screening.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, efforts toward early detection and early optimal intervention are needed for mild AIS before it progresses and worsens the associated deformities in order to reduce the number of patients who require surgical treatment. Hence, several researchers and physicians recommend school screening for scoliosis, but this entails unnecessary excessive costs12,13,14,15 ) . In South Korea, the screening program has been subsidized by the government or hospitals; however, results are available only for some areas and suggest only prevalence16 ) .…”
Section: Introductionmentioning
confidence: 99%